ANALISIS FAKTOR PENYEBAB KETIMPANGAN PENDAPATAN PADA LIMA PROVINSI TERTIMPANG DI INDONESIA - Hikmah Nurain (2022)
This research was conducted to find out the effect of economic growth, the human development index, the provincial minimum wage, and the realization of provincial government capital expenditures on the level of income inequality. This research uses five provinces with the highest inequality including the Special Region of Yogyakarta, Gorontalo, West Java, DKI Jakarta, and Papua. The sample determination uses a saturated sampling technique with 5 provinces during 2015-2020, so the total sample is 30 data. The data that is processed in this research is in the form of secondary data sourced from the Central Statistics Agency (BPS). Associated with the implementation of testing to prove the existing hypothesis in this research, used multiple linear regression method with panel data analysis and program Eviews 10 as a testing tool with a significance level of 5% (0.05). Partially, the results show that the human development index, the provincial minimum wage, and the realization of provincial government capital expenditures have a significant effect on income inequality, while economic growth has no effect. The results also show that simultaneously the four independent variables affect income inequality.